FAKTOR-FAKTOR YANG MEMPENGARUHI KEPATUHAN WAJIB PAJAK ORANG PRIBADI DI KOTA SEMARANG (Studi Empiris Di KPP Pratama Semarang) (Students' Journal of Accounting and Banking, 2015)
The purpose of this research is to analyze the influence of tax Knowledge, awareness of taxation, taxpayer environment, attitude of fiscus, socialization of taxation, and tax penalties against individual taxpayer compliance in Semarang city. The population in this research is the individual taxpayer who runs a private enterprise in the region of KPP Pratama Semarang. The sampling technique used is proportional sampling with sample size is 100 respondents. Based on the test has done, the results are the taxpayers environment variable, attitude of fiscus, socialization of taxation, and tax penalties have significant positive effect on tax compliance. But tax knowledge variable has significant negative effect on tax compliance and awareness of taxation variable has no effect on tax compliance.Keywords: Tax Knowledge, Awareness of Taxation, Taxpayer Environment, Attitude of Fiscus, Socialization of Taxation, Tax Penalties, and Tax Compliance